CORRELATION BETWEEN TOTAL NASAL SYMPTOM SCORE AND CLASSIFICATION OF RHINITIS ALLERGY BASED ON ARIA-WHO WITH ASTHMA COMORBIDITY AT PHC HOSPITAL IN SURABAYA - Azzahra Shalsabila Yuwono; Wiyono Hadi; Zenia Angelina (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction: The prevalence of Rhinitis Allergy (RA) is quite high, reaching 32%. The incidence of RA is often associated with asthma, as many as 45% of asthmatics occur after RA, and as many as 20-50% of RA occur after asthma. If RA occurs together with asthma, it can exacerbate clinical symptoms for the patient. According to ARIA-WHO, RA is classified according to time, into intermittent and persistent, and based on the severity of symptoms and quality of life, divided into mild and moderate-severe. Currently, there is a short questionnaire, namely the Total Nasal Symptom Score (TNSS). TNSS is the sum of individual scores for each nasal symptom. Each symptom was measured using a score of 0 to 3.Purpose: To determine the correlation between TNSS and RA classification based on ARIA-WHO with asthma comorbidity at PHC Hospital in Surabaya.Method: This study used an observational analytic research design with a cross-sectional study design, with a sample size of 39. Statistical analysis was carried out using the Spearman Correlation test.Result: From 39 samples, female (59%) and male (41%), the highest age group was 46-55 years (28.2%), the most allergy history was allergy to cold and dust (67.9%), the highest degree of TNSS was mild (43.6%) followed by moderate (33.3%), then severe (12.8%) and very mild (10.3%). The highest degree of RA was persistent moderate-severe (51.3%), followed by mild persistent (17.9%), followed by intermittent mild and intermittent moderate-severe (15.4%). Based on the analysis results that have been carried out using the Spearman correlation test, the results are p = 0.000 (α = <0.05) and r = 0.566, showing a strong significant correlation.Conclusion: There is a strong significant correlation between TNSS and RA classification based on ARIA-WHO in RA patients with asthma comorbidity.